2023
DOI: 10.1177/00034894221143579
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Social Deprivation on Patient Satisfaction in Otolaryngology Clinics

Abstract: Objectives: Multiple factors have been associated with lower satisfaction scores. We hypothesize that patients with a more deprived socioeconomic status will have different patient satisfaction scores than patients of higher socioeconomic status. Methods: We reviewed Press Ganey satisfaction scores for new, outpatient visits between January 1, 2014, and December 31, 2018. Due to the high ceiling effects of the survey, “satisfaction” was defined as achieving a perfect score of 100. We determined social deprivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…ADI as a predictor of outcomes has been used in very few studies in rhinology. 31,32 The data in the study indicates that race and ADI are important factors that should be considered when tailoring postoperative care for patients undergoing ESS. Further research is needed to uncover the impact of race and ADI on presentation and outcomes of patients with CRS.…”
Section: Discussionmentioning
confidence: 94%
“…ADI as a predictor of outcomes has been used in very few studies in rhinology. 31,32 The data in the study indicates that race and ADI are important factors that should be considered when tailoring postoperative care for patients undergoing ESS. Further research is needed to uncover the impact of race and ADI on presentation and outcomes of patients with CRS.…”
Section: Discussionmentioning
confidence: 94%
“…22,23 Within otolaryngology, ADI has been used to examine potential disparities following oral cavity cancer surgery and patient satisfaction in otolaryngology clinics. 24,25 Liao and colleagues demonstrated that ADI is correlated with increased length of stay and cost following pediatric tracheostomy, 26 whereas Cheung and colleagues were unable to find a significant association between ADI and outcomes following pediatric adenotonsillectomy for sleep disordered breathing. 27 There remain, however, no studies which have used the index to investigate inequities in deep-neck infections such as RPA.…”
Section: Introductionmentioning
confidence: 99%
“…Notable associations with ADI include increased rates of hospital readmission and increased incidence of COVID‐19 22,23 . Within otolaryngology, ADI has been used to examine potential disparities following oral cavity cancer surgery and patient satisfaction in otolaryngology clinics 24,25 . Liao and colleagues demonstrated that ADI is correlated with increased length of stay and cost following pediatric tracheostomy, 26 whereas Cheung and colleagues were unable to find a significant association between ADI and outcomes following pediatric adenotonsillectomy for sleep disordered breathing 27 .…”
Section: Introductionmentioning
confidence: 99%